2016
DOI: 10.5489/cuaj.3628
|View full text |Cite
|
Sign up to set email alerts
|

Robotic prostatectomy is associated with increased patient travel and treatment delay

Abstract: Introduction: New technologies may limit access to treatment. We investigated radical prostatectomy (RP) access over time since robotic introduction and the impact of robotic use on RP access relative to other approaches in the modern era.Methods: Using the National Cancer Data Base, RPs performed during the eras of early (2004‒2005) and late (2010‒2011) robotic dissemination were identified. The primary endpoints, patient travel distance and treatment delay, were compared by era, and for 2010‒2011, by surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…While surgery may seem appealing to some patients living in rural areas due to the logistic of one-time travel, 30 this study shows that patients living in rural areas are still less likely to undergo surgery. A similar trend has been observed in the United States and Australia where rural dwellers were less likely to undergo surgery for their PCa, 13,14,[31][32][33][34] which the authors of these studies attributed to the longer travel distance to the centralized urban treatment centers, access to health care providers, and the geographical differences in the management of patients. 14,31,33,34 Given PCa surgery in Saskatchewan is also centrally administered in the CMAs of Regina and Saskatoon, living in rural parts of the study area may be a proxy for needing longer travel to the Saskatchewan PCa assessment centers (compared to greater urban areas).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…While surgery may seem appealing to some patients living in rural areas due to the logistic of one-time travel, 30 this study shows that patients living in rural areas are still less likely to undergo surgery. A similar trend has been observed in the United States and Australia where rural dwellers were less likely to undergo surgery for their PCa, 13,14,[31][32][33][34] which the authors of these studies attributed to the longer travel distance to the centralized urban treatment centers, access to health care providers, and the geographical differences in the management of patients. 14,31,33,34 Given PCa surgery in Saskatchewan is also centrally administered in the CMAs of Regina and Saskatoon, living in rural parts of the study area may be a proxy for needing longer travel to the Saskatchewan PCa assessment centers (compared to greater urban areas).…”
Section: Discussionsupporting
confidence: 68%
“…7 Multiple studies have shown that patients living in rural regions may compromise their cancer treatment decision, [8][9][10][11][12][13][14] notably due to longer travel time and distance to access treatment centers. 8,9,14 Because Saskatchewan has a relatively large rural population, 15 Saskatchewan PCa patients living in rural geographic locations may face these issues regarding accessibility to health care services including cancer treatments. [3][4][5][6] Hence, PCa patients might choose their PCa treatments based on where they reside rather than the optimal treatments available for their PCa pathology.…”
mentioning
confidence: 99%
“…[1][2][3][4] With SWT on the rise in Canada, 5 it is important to question its impact on prostate cancer pathological outcomes, particularly for men awaiting robot-assisted radical prostatectomy (RARP) due to limited access to such technology. 6,7 In the era predating robotic surgery in Canada, a systematic review of the literature by Saad et al in 2006 reported that the median wait time for prostatectomy varied from 42 days (consultation to operation) to 83 days (consultation to hospital admission). 8 Furthermore, their review demonstrated that Canada, unlike other comparable industrialized countries, seemed to have a steadily increasing wait time.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although our study included more very lowand low-volume than intermediate-and high-volume hospitals, it is not realistic that there have been no robotic RPs performed in hospitals other than the ones with a high yearly RP volume. Furthermore, in comparison to our data, data from Canada showed that within a time period of 1 year (2010-2011), 74, 21 and 4.3% of RPs were robotic, open, and laparoscopic respectively [13]. The data from Canada also showed that laparoscopic radical prostatectomy (LRP) and robot-assisted radical prostatectomy (RARP) were more likely to be performed at academic and high-volume centres compared to open radical prostatectomy (ORP).…”
Section: Discussionmentioning
confidence: 82%